2007
DOI: 10.1080/15476910601119350
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Immunotoxic Potentials of Metals Are Governed by Select Physicochemical Properties: Vanadium Agents

Abstract: The in situ reactions of metal ions/complexes are important in understanding the mechanisms by which environmental and occupational metal particles alter lung immune responses. A better understanding of these reactions in situ will also allow for the improved specificity and controlled toxicity of novel metallocompounds to be used as inhaled diagnostics or therapeutics. Our previous work showed that inhalation of metals (e.g., chromium, vanadium, nickel) caused altered lung immune cell function and host resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Recently in vivo vanadium toxicological studies using decavanadate showed that in hepatic and cardiac muscle cells, the degree of vanadate toxicity depends on the nature of the compounds and whether they are administered by intraperitoneal or intravenous methods [31]. This conclusion is in agreement with other vanadium compounds [16,46,47]. The response to decavanadate in vanadium accumulation, lipid peroxidation and oxidative stress markers [48] and yeast growth responses [26,27,49], is significantly different than that observed for the simple monomeric vanadate.…”
Section: Introductionsupporting
confidence: 53%
“…Recently in vivo vanadium toxicological studies using decavanadate showed that in hepatic and cardiac muscle cells, the degree of vanadate toxicity depends on the nature of the compounds and whether they are administered by intraperitoneal or intravenous methods [31]. This conclusion is in agreement with other vanadium compounds [16,46,47]. The response to decavanadate in vanadium accumulation, lipid peroxidation and oxidative stress markers [48] and yeast growth responses [26,27,49], is significantly different than that observed for the simple monomeric vanadate.…”
Section: Introductionsupporting
confidence: 53%
“…Vanadium induced apoptosis of cells associated with elevated ROS levels and ROS-related signal transduction [23,24], while antioxidants, either as complex ligands [25] or co-administration [26,27], significantly reduced vanadium toxicity. Stimulation of ROS production by vanadium varied depending on redox activity of vanadium species [9,28]. Vanadium compounds with various ligands and oxidative number may act on mitochondria differently.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recently the effects of V5 dipic was found to be different than the corresponding vanadium(IV) and (III) dipicolinate complexes in lowering the elevated blood glucose and lipid levels in Wistar rats with STZ induced diabetic rats [29]. In addition, the toxicity of the V5 dipic complex was found to be different than that of the vanadium(IV) and (III) dipicolinate complexes [35].…”
Section: Resultsmentioning
confidence: 99%
“…A larger fraction of BMOV is likely to remain intact during the assays and the amavadine analog is expected to remain intact during the duration of these experiments [19,33,34]. These predictions are based on chemical studies that the V5 dipic complex hydrolyze and reduce at neutral pH, and that BMOV oxidize in the presence of air [30,31] as well as studies in biological in which these compounds were found to provoke different responses [18,29,33,35]. The structures of the above vanadium complexes, as well of the vanadate oligomers are described elsewhere [15,19].…”
Section: Methodsmentioning
confidence: 99%